The Impact of Computerized Procurement on the Effectiveness of a Firm - Adeline Nalumu (Uganda Christian University, 2023)
The study examined the impact of computerized procurement on the effectiveness of a firm: a case of Ceva Inter freight Uganda Limited. It specifically focused on the efficiency of procurement processes, cost savings, and cost management, data accuracy and decision making, supply chain visibility and performance, and other factors of improving effectiveness of Ceva inter freight Uganda Limited. The study was carried out using a cross sectional research design where both quantitative and qualitative research approaches were also used. The data was collected using questionnaires and interviews during the data collection, both purposive and stratified sampling methods were used. A sample size of 52 respondents who were management and employees of Ceva inter freight was also used in the study. This study found out that computerized procurement plays a valuable role throughout the procurement lifecycle of a firm and offers concrete opportunities for local and national government to improve their performance in terms of transparency, participation, and decentralization by narrowing the constraints of geographical isolation or insufficient time, also has the potential to invigorate business relations allowing citizen participation in firm activities. However, the study also highlighted challenges affecting the effectiveness of Ceva inter freight including limited financial resources, limited research, and innovation, limited skilled personnel, limited technical support, inappropriate technologies, and limited management commitment. Overcoming these challenges is crucial for organizations to fully realize the impact of computerized procurement on the effectiveness of Ceva inter freight Uganda Limited. The study recommended that Ceva inter freight Uganda limited should conduct staff training or job training for computerized staff. It also recommended that Companies should select appropriate technology or platforms to have and maintain the quality of information provided by computerized procurement. The selection of computerized procurement platforms should also consider the type of organizations and users who use them.
This is a dissertation.